Molecular Detection of Urease and Hemolysine Genes in Proteus Mirabilis Bacteria Isolated From Urine of Rheumatoid Arthritis Patients in Najaf Province - Shaker, Hawraa Hussein Tawfiq; Thamer, Sarah Adil Mohsen; Bedeir, Imad Ali Mutasher; Kadim, Rajaa Obaid Jebur; Khudhair, Sameh Mohammed Oudah (American Journal of Biology and Natural Sciences, 2025)
Proteus mirabilis is a known uropathogen with significant virulence factors implicated in urinary tract infections (UTIs), particularly among patients with rheumatoid arthritis (RA). Despite prior studies, the molecular relationship between P. mirabilis virulence genes and RA remains underexplored. This study aimed to isolate P. mirabilis from the urine of RA patients, assess its antibiotic resistance profile, and detect the presence of two key virulence genes: urease (ureC) and hemolysin (hpmA). Using standard microbiological techniques, biochemical tests, antibiotic susceptibility assays, and PCR analysis, the study found that P. mirabilis was the most prevalent pathogen (51%) among 50 RA patients. All isolates showed complete resistance to cefotaxime, amoxicillin, and ampicillin, while being 100% sensitive to meropenem, levofloxacin, and ciprofloxacin. Molecular analysis revealed that all P. mirabilis isolates harbored both ureC and hpmA genes. These findings suggest a potential pathogenic link between P. mirabilis virulence and RA, underscoring the need for further molecular and immunological studies to understand microbial triggers in autoimmune disorders.